2020
DOI: 10.9734/ajgr/2020/v3i330106
|View full text |Cite
|
Sign up to set email alerts
|

Copper Concentration and Distribution in the Ground Water of Delta State Polytechnic, Ozoro, Nigeria

Abstract: Copper toxicity in the ecosystems have becomes a global concern in recent times; therefore, there is need to curtail the increment of copper concentration within the environment. In this study, a total of 67 ground water samples were collected from the premises of Delta State Polytechnic, Ozoro, at a depth of 90 cm. The water samples were collected during the peak of the rainy season (September 2019); when the water table of the study area was very high, close to the soil surface. Copper concentration of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Iron contamination owes its origin to the presence of origin fixing bacteria associated with sedimentary organic matter [44] as well as low pH values causing corrosion of iron, clogging of distribution pipes and an objectionable odour [45]. The occurrence of iron in water distorts the appearance of water, making it turbid with a unique colour that is yellow brown to black [46]. Iron discolouration and the metallic taste occur at concentrations that exceed 1.0 mg/l [44].…”
Section: Heavy Metal Contentmentioning
confidence: 99%
“…Iron contamination owes its origin to the presence of origin fixing bacteria associated with sedimentary organic matter [44] as well as low pH values causing corrosion of iron, clogging of distribution pipes and an objectionable odour [45]. The occurrence of iron in water distorts the appearance of water, making it turbid with a unique colour that is yellow brown to black [46]. Iron discolouration and the metallic taste occur at concentrations that exceed 1.0 mg/l [44].…”
Section: Heavy Metal Contentmentioning
confidence: 99%
“…This irregularity could be attributed to the variation in the soil geotechnical and physiochemical properties, along the testing area [2]. Previous research [15,23] depicted that metals ions varied widely across the study region (university premises). Similar results were obtained by [13], where the soil resistance at some locations at the Federal University of Technology, Akure, Nigeria fluctuated with increased in the probe distance.…”
Section: Earth's Resistancementioning
confidence: 99%
“…The high heavy metals contamination factors recorded at the Ozoro road, against the values recorded at Ughelli and irri roads, could be attributed to the leachates seepage from the dumpsite near (about 250 m) the collection point. Akpomrere [41] reported that leachates from dumpsite are able to increase heavy metals concentrations in the soil and water bodies; thus, their locations should be sited at a safer distance from sources of drinking water and other agricultural activities.…”
Section: Contamination Factor and Enrichment Factormentioning
confidence: 99%